2019
DOI: 10.1063/1.5108698
|View full text |Cite
|
Sign up to set email alerts
|

Singlet fission of amorphous rubrene modulated by polariton formation

Abstract: The excited-state dynamics of molecular aggregates are governed by their potential energy landscape that can hardly be controlled artificially. However, it is possible to alter the excited state dynamics by a strong coupling between light and molecules (polariton formation) because it can decouple the electronic and vibrational degrees of freedom. Here, we demonstrate this polaron decoupling effect on the photochemical dynamics in singlet fission (SF) of amorphous rubrene thin films embedded in optical microca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 56 publications
3
75
0
Order By: Relevance
“…Recent experiments with rubrene microcavities [143] confirm the validity of the HTC model to describe the optical response and chemical reactivity of molecular polaritons in the optical regime, thus consolidating the quantum optics approach to describe these systems.…”
Section: B Recent Theoretical Progressmentioning
confidence: 86%
See 1 more Smart Citation
“…Recent experiments with rubrene microcavities [143] confirm the validity of the HTC model to describe the optical response and chemical reactivity of molecular polaritons in the optical regime, thus consolidating the quantum optics approach to describe these systems.…”
Section: B Recent Theoretical Progressmentioning
confidence: 86%
“…There are several widely-used technologies that ultimately base their efficiency on the rates of chemical reactions or electron transfer processes that occur in excited electronic states (e.g., sunscreens, polymers, catalysis, solar cells, OLEDs). Therefore, the ability to manipulate the rates and branching ratios of these fundamental chemical processes in a reversible manner using light-matter interaction with a vacuum field, suggests a promising route for targeted control of excited state reactivity, without exposing fragile molecular species or materials to ESC Cavity-enhanced energy transfer and conductivity in organic media [30,[137][138][139] ESC/VSC Strong coupling with biological light-harvesting systems [44,[140][141][142] ESC Cavity-modified photoisomerization and intersystem crossing [28,104,[143][144][145] ESC Strong coupling with an individual molecule in a plasmonic nanocavity [95,96,98,146] ESC Polariton-enhanced organic light emitting devices [32,35,147,148] EUSC Ultrastrong light-matter interaction with molecular ensembles [29,36,92,147,[149][150][151] VSC/VUSC Vibrational polaritons in solid phase and liquid phase Fabry-Perot cavities [38-40, 45-47, 49-54, 152] VSC Manipulation of chemical reactivity in the ground electronic state [43,55,153] ESC Cavity-controlled intramolecular electron transfer in molecular ensembles. [134,[154][155]…”
Section: A Recent Experimental Progressmentioning
confidence: 99%
“…Intramolecular vibrations have been suggested to assist the relaxation of organic exciton–polaritons en route to condensation 1017 and are intensively explored in relation with different properties of exciton–polaritons. 1820 According to theoretical works, which focus on few-level systems describing optical transitions coupled to a single high-frequency vibrational mode, the process of exciton–polariton relaxation from the reservoir to the bottom of the dispersion curve is assisted by emission of a vibrational quantum in the electronic ground state of the molecules. 11,21 Despite these theoretical studies, no direct experimental evidence of this relaxation mechanism toward condensation has been reported, and the existing experimental literature has thus far focused on the dynamics of exciton–polaritons in the linear regime, 2226 leaving the nonlinear relaxation dynamics of organic-based condensates unexplored.…”
mentioning
confidence: 99%
“…In a next step, we have deposited Zn-SiPc SURMOFs of various thicknesses on SAM-modied Ag substrates, simply by using different numbers of immersion cycles. In following previous approaches, 6,[38][39][40] this thin lm was converted into an optical cavity by coating with a $10 nm semi-transparent Ag top layer (Fig. 1a) using a metal evaporator.…”
Section: Surmof In Optical Cavitymentioning
confidence: 99%
“…[1][2][3] The strong coupling of optical and electronic states can give rise -oen in counterintuitive waysto new functionalities. In this emerging eld, the new phenomena are not limited to the optical regime; [4][5][6] in previous works it has been demonstrated that such quantum-electro-dynamical (QED) phenomena can affect many more molecular properties, including vibrational transitions, chemical reactivity landscapes, and electronic properties. [7][8][9] When an organic or inorganic compound is introduced into an optical cavity (for example, by sandwiching it between two mirrors), electronic states of the molecular moieties can resonate with the eigenmodes of the cavity and give rise to two new polaritonic states, P+ and PÀ (Rabi splitting).…”
Section: Introductionmentioning
confidence: 99%